Codification, meritocracy and performativity: Debilitating factors for black pre-service teachers - P. B. N. Maseko (Perspectives in Education, 2018)
This article presents an argument and commentary about the concomitant effects of codification, meritocracy and performativity in the academic performance of a cohort of black African Foundation Phase Bachelor of Education degree students at a previously predominantly white institution of higher learning. The objective of this paper is to illustrate the point that the combination of codification, meritocracy and performativity has potentially debilitating ramifications for the performance of this cohort of pre-service teachers. In this instance, language is a codification mechanism and a means towards epistemological access. This paper posits the viewpoint that the sociocultural backgrounds of the cohort predispose them to the resultant negative effects of the combination of the three factors. The study that forms the basis of this article used the qualitative theoretical orientation of the transformative paradigm to pursue a critical emancipatory and transformative theoretical agenda. This agenda is embodied in the recommendations that are informed by an infusion of the literature, the participants’ observations, as accrued from the data, and the researcher’s reflections. The intention of this social-justice-oriented support strategy is to make an implied decolonial contribution towards counteracting and diffusing the potentially debilitating effects of the combination of codification, meritocracy and performativity.